O humor nos roteiros de “A comédia da vida privada” : uma visão a partir de seus diálogos - Fischer, Janaína Daudt (2016)
Is there a “Guel Arraes way” (Guel Arraes Center, Globo TV) to create television content? And if so, would this production only be possible in a specific time and place? How are the comic techniques used in the production of meaning in dialogue scriptwriting? These and other issues are covered in this research, which analyzed the dialogues of twelve scripts of the series “The Comedy of Private Life”, produced and aired by Globo TV from 1995 to 1997, created by Guel Arraes Center. The methodological approach proposes a link between the tools of Film Analysis and the perspective of Cultural Studies (using as inspiration the Cultural Circuit of Richard Johnson) in order to infer the relationship between the writer, the writing and the lived cultures that form and are formed both by producers and spectators. Some categories were created, based mainly on the reading of Henri Bergson’s book “Laughter”, such as “inversion”, “repetition”, “intelligence opposed to emotion” and “ethical dimension of humor”, among others. The analysis sought to integrate these categories with Brazilian cultural aspects, inspired by authors like Roberto DaMatta and Mirian Goldenberg. An interview with the director Guel Arraes also makes up the reference’s framework of this research, as well as readings on narrative, humor, comedy, scriptwriting and dialogues. Among the final considerations, we should highlight that is noticed direct relationship between the analyzed dialogues and aspects of Brazilian culture of the late twentieth century, and it is considered that there is a “positioning” of the authors from which they communicate a vision of Brazil. The research aims to contribute to the theoretical study on the practice of writing comic dialogues on scripts for Brazilian television.